Tracing toxic chemical releases embodied in U.S. interstate trade and their unequal distribution - Guangxiao Hu; Kuishuang Feng; Laixiang Sun; Giovanni Baiocchi (Environment International, 2023)
Toxic chemicals have severe impacts on ecosystem, climate change and human health, and the current toxic releases are inequitably distributed across regions. Investigating the toxic release embodied in final demand by states and income groups can reveal the responsibility transfer of different entities. In this paper, we extended the U.S. multi-regional input–output (MRIO) model with toxic chemical release data in 2017 to conduct the production- and consumption-based accounting of toxic release by each state, and the inter-regional transfer of embodied toxic release between states. In addition, this paper analyzed how the toxic releases and inter-state transfer of embodied toxic release have been driven by income groups across states. The results showed that the toxic release from production was highly concentrated on the central states and the Great Lakes Region, while the consumption-based accounting of toxic release was more equally distributed across regions in the US. The non-metallic and metallic products manufacturing sectors were the most important sectors for most states from both production and consumption-based perspectives and were also the most essential sectors for interregional flows of embodied toxic release from Great Lake Region to Southeast, Mid-Atlantic and Northeast. Our results also showed that the largest portion (41.88%) of embodied toxic releases were triggered by households’ final demand, and that the consumption of the richest 35% of households contributed to more than 50% of the total toxic chemical releases triggered by total final demand of all households.